2017
DOI: 10.7554/elife.21074
|View full text |Cite
|
Sign up to set email alerts
|

Direct measurement of TRPV4 and PIEZO1 activity reveals multiple mechanotransduction pathways in chondrocytes

Abstract: The joints of mammals are lined with cartilage, comprised of individual chondrocytes embedded in a specialized extracellular matrix. Chondrocytes experience a complex mechanical environment and respond to changing mechanical loads in order to maintain cartilage homeostasis. It has been proposed that mechanically gated ion channels are of functional importance in chondrocyte mechanotransduction; however, direct evidence of mechanical current activation in these cells has been lacking. We have used high-speed pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
271
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 210 publications
(285 citation statements)
references
References 81 publications
14
271
0
Order By: Relevance
“…The inactivation kinetics of the currents observed in vector-transfected cells were slow, and do not resemble those observed when Piezo1 is overexpressed in HEK cells (Fig.1c left)(Bae et al, 2011; Coste et al, 2010). However, slower inactivation kinetics of Piezo1-dependent currents in other cell types has been observed in cell-attached recordings (Bae et al, 2015; Lee et al, 2014; Pathak et al, 2014; Peyronnet et al, 2013; Servin-Vences et al, 2017). We previously created a more reliable mechanically silent cell line for expression studies by inactivating endogenous Piezo1 in HEK cells (HEK-P1KO) using CRISPR/Cas9 to truncate all Piezo1 alleles (Lukacs et al, 2015).…”
Section: Resultsmentioning
confidence: 95%
“…The inactivation kinetics of the currents observed in vector-transfected cells were slow, and do not resemble those observed when Piezo1 is overexpressed in HEK cells (Fig.1c left)(Bae et al, 2011; Coste et al, 2010). However, slower inactivation kinetics of Piezo1-dependent currents in other cell types has been observed in cell-attached recordings (Bae et al, 2015; Lee et al, 2014; Pathak et al, 2014; Peyronnet et al, 2013; Servin-Vences et al, 2017). We previously created a more reliable mechanically silent cell line for expression studies by inactivating endogenous Piezo1 in HEK cells (HEK-P1KO) using CRISPR/Cas9 to truncate all Piezo1 alleles (Lukacs et al, 2015).…”
Section: Resultsmentioning
confidence: 95%
“…TRPV4 ion channel can be activated by various stimuli, including osmotic stress, mechanical loading, and heat. TRPV4 plays a key role in regulating calcium homeostasis and matrix metabolism in cartilage, while TRPV4‐dysfunction is associated with the development of osteoarthritis . In the compressed cartilage, both mechanical loading and osmotic stress can activate the TRPV4 channel and initiate the [Ca 2+ ] i transients.…”
Section: Resultsmentioning
confidence: 99%
“…VGCCs play critical roles in the differentiation, proliferation, and metabolic activities of chondrocytes (55). We previously showed that blockage of T‐type VGCC reduced load‐induced osteoarthritis in mice (51). The functions of VGCCs in the spontaneous calcium signaling of chondrocytes may further reveal their roles in osteoarthritis development and be worth future research efforts.…”
Section: Discussionmentioning
confidence: 99%
“…8 ) Mechanosensitive ion channels: Sample was treated with 20 µM GdCl 3 . 9 ) TRPV4 channel: 10 µM GSK205 was used to block the TRPV4 channel (16, 51). 10 ) Voltage‐gated calcium channel (VGCC): 17.7 µM NNC 55‐0396 was used to block the T‐type VGCC (52, 53); 100 µM verapamil was used to block the L‐type VGCC (5456).…”
Section: Methodsmentioning
confidence: 99%